PENGARUH INTELLECTUAL CAPITAL, CAPITAL STRUCTURE, DAN FIRM’S SIZE TERHADAP FINANCIAL PERFOMANCE - Elsa Florentia; Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to determine the positive or negative effect of intellectual capital, capital structure, and Firm’s size on firm’s financial performance that is conducted on 28 bank sector listed companies in Indonesia Stock Exchange period year 2017-2019 in forms used of panel data. The data panel analysis fixed effect model which conducted using Microsoft Excel and E Views 11 software. Intellectual capital proxied by value added capital employed and Intellectual capital efficiency, capital structure proxied by debt-to-equity ratio, and firm’s financial performance proxied by return-on-asset. The result of this study are: (1) Value added Capital employed and Debt to Equity Ratio significantly positive effect on firm’s financial performance (2) Intellectual capital efficiency significantly positive effect and debt-to-equity-ratio significantly negative effect only on return-on-asset. (4) Fim’s Size have significant negative effect on firm’s financial performance.The implication of this study is need for company awareness to improve of financial perfomance through intellectual capital.